Using Runtime Paths for Macro Analysis - Chen, Mike; Kiciman, Emre; Accardi, Anthony; Fox, Armando; Brewer, Eric (9th Workshop on Hot Topics in Operating Systems, 2003)
We introduce macro analysis, an approach used to infer the high-level properties of dynamic, distributed systems, and an indispensable tool when faced with tasks where local context and individual component details are insufficient. We present a new methodology, runtime path analysis, where paths are traced through software components and then aggregated to understand global system behavior via statistical inference. Our approach treats components as gray boxes and complements existing micro analysis tools, such as code-level debuggers. We use runtime paths to deduce application state, detect failures, and diagnose problems, all in an application-generic fashion.